The Perspective of Children Right in the Children Mobilization of Political Campaign In Indonesia - Fikri, Haidar (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
Politic cannot be separated by mass mobilization. In several definitions, mass mobilizationis also defined as a political campaign. Nowadays, campaign of political party does not payattention to the regulation. The party involves the children in campaign. There are manychildren join the campaign. It can be seen when the campaign gathers in a certain placewith mass mobilization. There are many children who are interested in campaign like theyare watching the concert of dangdutmusic or other entertainments. Besides that, the showof campaign in television also influences the children right.Many children memorize themars of political party and they always sing it because it is always played in TVadvertisement in Indonesia. It absolutely breaks the law no 23 of 2002 and no. 35 of 2014about children protection. After being investigated, the children memorize the mars ofpolitical party from television that is broadcasted massively everyday. This researchfocuses on how children mobilization in a campaign through the perspective of childrenright. This research used the approach of law no 23 of 2002 and no 35 of 2014 aboutchildren protection. The method of the research used document study from various sourcessuch as media, journal, and other documents. The result of the research shows that manypolitical parties ignore the children right. It is usually found that children join the campaign.The party has not understood the law of general election. The parents also have role toobserve their children when they are watching TV because the play of mars of a politicalparty is not appropriate with children right. Therefore, parents must accompany the childrenwhile watching TV in order that their right can be accomplished related to politic.Key words: children right, campaign, political party